Gambaran Pengetahuan dan Sikap Ibu dalam Pencegahan Dehidrasi pada Anak Usia Balita Diare di Puskesmas Bangetayu - Muliatun Naili Syahadah; Indra Astuti; Nopi Nur Khasanah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Background: Dehydration is a prevalent consequence of the condition noticed in pediatric patients presenting to the Emergency Department (ER). Dehydration transpires when the excretion of water exceeds its intake, followed by the concomitant loss of electrolytes. This research aims to assess mother knowledge and attitudes on the prevention of dehydration in children under five years old suffering from diarrhea. Method: This research employs a descriptive methodology with a survey design, including 53 participants who are moms of toddlers. Data was gathered via a questionnaire assessing the knowledge and attitudes of mothers with children under five about dehydration prevention. This research employs purposive sampling and encompasses two types of data: categorical and numerical. Categorical data comprises respondent traits, knowledge, and attitudes, while numerical data pertains to age.. Results: The study revealed that among 53 respondents, 20 (37.7%) exhibited characteristics of early adulthood (ages 26-35). All respondents were female, totaling 53 (100.0%). The predominant educational attainment among respondents was high school/vocational school, with 21 individuals representing 39.6% of the total respondents. The sample included 38 moms, of whom 71.7% were non-employed or homemakers. The predominant religious affiliation among respondents was Islam, with 47 individuals (88.7%), followed by 5 Protestant Christians (9.4%) and 1 Catholic Christian (1.9%). Furthermore, statistics about respondents' knowledge indicated that 4 respondents (7.5%) exhibited bad results. Among 53 respondents, 25 (47.2%) shown excellent knowledge, while 24 (45.3%) displayed adequate knowledge. Data on attitudes revealed that, among the 53 respondents, 16 (30.2%) exhibited a positive attitude, 33 (62.3%) demonstrated a satisfactory attitude, and 4 (7.5%) displayed a negative attitude.. Conclusion: Efforts are still needed to improve knowledge and attitudes in the prevention of dehydration in children under five because from the results of the study there are still respondents with less knowledge and attitudes.